Temperature dependence of the vapor pressure and evaporation coefficient of supercooled water. Issue 18 (27th September 2014) - Davies, James F.; Miles, Rachael E. H.; Haddrell, Allen E.; Reid, Jonathan P.
Abstract We report measurements of the vapor pressure of water over the supercooled temperature range 248 to 273 K derived from evaporation kinetics measurements of single water droplets. Accurate measurements of the relative humidity of the surrounding gas phase are derived from comparative and sequential measurements of the evaporation kinetics of droplets containing sodium chloride. The temperature dependence of the vapor pressure of supercooled water is shown to conform closely to the parameterization provided by Murphy and Koop (2005) once the uncertainties in experimental and thermophysical parameters are accounted for by ensuring an accurate representation of evaporation rates at temperatures above 273 K. Further, from a sensitivity analysis of all of the data over the full temperature range from 248 to 293 K, we can conclude that the evaporation coefficient of water, and thus the mass accommodation coefficient, is greater than, or equal to, 0.5.